Introduction and Application of a Simple Probabilistic Liquefaction Hazard Analysis Program: HAZ45PL Module. (27th January 2021) - Chou, Jui-Ching; Hsieh, Pao-Shan; Lin, Po-Shen; Yen, Yin-Tung; Lin, Yu-Hsi
Abstract : The 2016 Meinong Earthquake hit southern Taiwan and many shallow foundation structures were damaged due to soil liquefaction. In response, the government initiated an investigation project to construct liquefaction potential maps for metropolitans in Taiwan. These maps were used for the preliminary safety assessment of infrastructures or buildings. However, the constructed liquefaction potential map used the pseudo-probabilistic approach, which has inconsistent return period. To solve the inconsistency, the probabilistic liquefaction hazard analysis (PLHA) was introduced. However, due to its complicated calculation procedure, PLHA is not easy and convenient for engineers to use without a specialized program, such as in Taiwan. Therefore, PLHA is not a popular liquefaction evaluation procedure in practice. This study presents a simple PLHA program, HAZ45PL Module, customized for Taiwan. Sites in Tainan City and Yuanlin City are evaluated using the HAZ45PL Module to obtain the hazard curve and to construct the liquefaction probability map. The liquefaction probability map provides probabilities of different liquefaction potential levels for engineers or owners to assess the performance of an infrastructure or to design a mitigation plan.